APLIKASI MONITORING PERSEDIAAN DENGAN METODE USER CENTER DESIGN PADA PT. SAHABAT JAYA CEMERLANG - Rahel Junita (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2018)
The development of increasingly rapid and modern technology has an influence on the way personal and organizational work. Especially in the business world, technological developments make it easier for business people to make more practical ways of working. In the business world, technology can be used as a tool to monitor activities that occur in the business including sales transactions and monitoring of available merchandise stocks, so the formulation of the problem in this proposal is how to make an application for monitoring beverage product data in an web-based warehouse effectively by implementing User Centered Design method. So with the monitoring of the stock of goods in the warehouse, it makes it easier for warehouse heads and managers to monitor or find out the stock of goods, incoming and outgoing goods effectively in real time. The system built can make it easy for warehouse staff to issue and enter goods using barcode scans without having to record goods manually.